PENERAPAN PENDEKATAN BERMAIN UNTUK MENINGKATKAN HASIL BELAJAR GERAK DASAR PERMAINAN BOLAVOLI MINI - Dwi Fitrianingsih; Budhi Satyawan (PHEDHERAL, 2017)
The purpose of this research is to improve learning outcomes basic of mini volleyball with implementation play approaches to learners iv a grade of mi muhammadiyah jimbung, in the academic year 2016/2017.This study close to practice clas action. Study held in 2 cycle consists of 4 steps in every cycle consists of planning, action, oservation and reflection. Subject in this study is learners of IV A MI Muhammadiyah Jimbung whichamounts to 22 learners, 12 male and 10 female. Data collection technique with test and observation. Data validation use triangulation data. Data analysis use descriptive qualitative with precentage tehnique.The result are 27,27% complete and 72,72% uncomplate. This first cycle obtained resut 59,09% complate and 40,91% uncomplate with averaage value of psychomotor 59,09%, affective 81,81% and cognitive 68,18%. Second cycle obtained results86,46% complate and 13,64% uncomplatewhith average value psychomotor 77,27%, affective 90,90%, and cognitive 81,81%. Based of analysis result from 2 cyclle show increase and suitable with achievement target.Conclusion on this study is implementation approaches can improve learning outcomes basic of mini volleyball on IV A MI Muhammadiyah Jimbung. In the academic year 2016/2017.